2021
DOI: 10.1111/phor.12389
|View full text |Cite
|
Sign up to set email alerts
|

Modelling extreme wide‐angle lens cameras

Abstract: The use of consumer cameras fitted with extreme wide‐angle (EWA) lenses for photogrammetric measurement is increasing. Conventional modelling of EWA systems relies on the pinhole camera model and up to five radial lens distortion terms. Aiming to reduce model complexity, this paper reports on an investigation into an alternate approach using fisheye lens models for EWA systems, despite them not falling strictly into the fisheye category. Four fisheye models were tested on four different cameras under laborator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…It requires that calibrated marks are placed at different depth-of-field positions in an indoor environment to encompass the entire image. Aimed to reduce model complexity, Lichti et al (2020Lichti et al ( , 2021 reported an alternate approach using fisheye lens models for consumer cameras with extreme wide-angle (EWA) lenses, which indicated that the number of radial distortion terms required for the fisheye model was lower in all cases; hence, model complexity was reduced. According to the constraint that space lines have to be mapped onto a straight line in a rectified image (Devernay and Faugeras, 2001), Zhang et al (2015) used three properly arranged long circular arcs to estimate the IOPs of fisheye cameras.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…It requires that calibrated marks are placed at different depth-of-field positions in an indoor environment to encompass the entire image. Aimed to reduce model complexity, Lichti et al (2020Lichti et al ( , 2021 reported an alternate approach using fisheye lens models for consumer cameras with extreme wide-angle (EWA) lenses, which indicated that the number of radial distortion terms required for the fisheye model was lower in all cases; hence, model complexity was reduced. According to the constraint that space lines have to be mapped onto a straight line in a rectified image (Devernay and Faugeras, 2001), Zhang et al (2015) used three properly arranged long circular arcs to estimate the IOPs of fisheye cameras.…”
Section: Related Workmentioning
confidence: 99%
“…Aimed to reduce model complexity, Lichti et al. (2020, 2021) reported an alternate approach using fisheye lens models for consumer cameras with extreme wide‐angle (EWA) lenses, which indicated that the number of radial distortion terms required for the fisheye model was lower in all cases; hence, model complexity was reduced. According to the constraint that space lines have to be mapped onto a straight line in a rectified image (Devernay and Faugeras, 2001), Zhang et al.…”
Section: Related Workmentioning
confidence: 99%
“…For this Heritage 2024, 7 2925 reason, some studies have recently focused on the improvement of this efficiency. Thus, some approaches have shown reductions in data acquisition work by increasing the field of view (FoV) of sensors, for example, in photogrammetry, through the use of wide-angle lenses [10][11][12][13][14], fisheye lenses [15][16][17][18][19][20][21][22][23][24], and 360-degree cameras [9,[25][26][27][28][29][30][31][32]. The recent use of fisheye images and panoramic images has made it possible to develop photogrammetric studies in complex scenes that had been almost impossible using conventional images.…”
Section: Introductionmentioning
confidence: 99%
“…3D modeling is the vectorial representation of the geometric information of an object in a computer environment. Today, 3D models of the physical earth or any object can be obtained by analyzing numerical data acquired using perspective imaging geometry and photogrammetric mathematical principles in a computer environment [1]. In addition, vectorial and visual presentations of the obtained 3D models can be made easily.…”
Section: Introductionmentioning
confidence: 99%